Fourier-based approach for power options valuation - Ibrahim, Siti Nur Iqmal; Ng, T. W. (Institute for Mathematical Research, Universiti Putra Malaysia, 2019)
In this study, we price options whose underlying asset is raised to a constant using the Fourier-Cosine (COS) method. The valuation is made within the Black-Scholes environment, where numerical experiments show that the COS method is more efficient than other known option pricing techniques.